Pointwise estimates for solutions to perturbed Hasegawa-Mima equations - Lijuan Wang (Electronic Journal of Differential Equations, 2015)
In this article, we study pointwise estimates for solutions to the two-dimensional perturbed Hasegawa-Mima equation based on the analysis of the Green functions for the linearized system. The pointwise estimates not only exhibit the Huygen's principle but also give additional insight on the description of the evolution behavior of the solution.